2014
DOI: 10.1021/cn500206a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Cannabinoid Based T-Type Calcium Channel Blockers with Analgesic Effects

Abstract: Low-voltage-activated (T-type) calcium channels are important regulators of the transmission of nociceptive information in the primary afferent pathway and finding ligands that modulate these channels is a key focus of the drug discovery field. Recently, we characterized a set of novel compounds with mixed cannabinoid receptor/T-type channel blocking activity and examined their analgesic effects in animal models of pain. Here, we have built on these previous findings and synthesized a new series of small organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 58 publications
2
39
0
Order By: Relevance
“…Cav3.2 null mice display a lower nociceptive response compared to wild-type mice in both phases of the formalin test [2,7,12] (Fig. 4).…”
Section: Kys-05090s Effects Depend On Cav32 Channelsmentioning
confidence: 95%
See 1 more Smart Citation
“…Cav3.2 null mice display a lower nociceptive response compared to wild-type mice in both phases of the formalin test [2,7,12] (Fig. 4).…”
Section: Kys-05090s Effects Depend On Cav32 Channelsmentioning
confidence: 95%
“…On the other hand, Cav3.2 knockout mice have reduced pain responses [7] and knockdown of Cav3.2 channels with antisense oligonucleotides by intrathecal injection mediated potent analgesia in different models of chronic pain [3]. Therefore, various blockers of Cav3.2 channels have been shown to mediate analgesia in models of inflammatory and neuropathic pain [1,2,11]. Some of the known T-type calcium channel inhibitors with analgesic actions have been shown to also block other types of ion channels, such as N-type calcium channels [13] and voltage-gated sodium channels [18] that are also important for the transmission of pain-related information.…”
Section: Introductionmentioning
confidence: 99%
“…This compound has completed phase1b clinical trials for pain and is being advanced into phase 2 trials. A series of compounds that combine the carbazole core of NMP-7 and features of Z944 also mediate potent Ca V 3 channel inhibition without off-target effects on cannabinoid receptors and with efficacy in several in vivo models of pain (Bladen et al, 2015). Another series of compounds that incorporates features of Z944 includes TTA-A2 [(R)-2-(4-cyclopropylphenyl)-N-(1-(5-(2,2,2-trifluoroethoxy) pyridin-2-yl)ethyl) acetamide] and TTA-P2 [3,5-dichloro-N-[1-(2,2-dimethyl-tetrahydro-pyran-4-ylmethyl)-4-fluoro-piperidin-4-ylmethyl]-benzamide] (Choe et al, 2011;Francois et al, 2013), both of which mediate state-dependent inhibition of T-type currents with a preference for Ca V 3.2.…”
Section: Ca V 3 Channel Pathophysiologymentioning
confidence: 99%
“…Some of these substances have not yet been tested in the clinic, whereas others have yielded Gagnon et al, 2013 KYS05090S or ABT-639. . Small-molecule T-channel blockers Jarvis et al, 2014;Zhang et al, 2015a;M'Dahoma et al, 2016 N-((1-(2-(tertbutylamino)-2-oxoethyl)piperidin-4-yl)methyl)-9-pentyl-9Hcarbazole-3-carboxamide CB2 agonist that targets Ca v 3.2 T-type channels Berger et al, 2014;Bladen et al, 2015;Snutch and Zamponi, 2017 A-1264087 State-dependent Ca v 2 blockers Oral administration of all of these drugs displays antiallodynic efficacy in rodent models (Patel et al, 2017) Under development Zamponi et al, 2015 Coull et al (2003) showed that a decrease in transmembrane chloride gradient occurred in rat dorsal horn lamina I neurons following peripheral nerve injury as a result of a reduction in expression of the potassium-chloride exporter, potassium-chloride exporter 2 (KCC2). The resulting accumulation of intracellular Cl 2 can cause normally inhibitory GABAergic, anionic, outward synaptic currents to become inward excitatory currents (Coull et al, 2003;Prescott et al, 2006).…”
Section: A Excitation-inhibition Balance In Neuropathic Painmentioning
confidence: 99%